Keefektifan Bakteri Endofit dan Fungi Mikoriza Arbuskula dalam Menekan Ralstonia solanacearum pada Tanaman Eucalyptus pellita - Susanti, Yuliana; Giyanto, Giyanto; Sinaga, Meity Suradji; Mutaqin, Kikin Hamzah; Tjahjono, Budi (Jurnal Fitopatologi Indonesia, 2022)
Effectiveness of Endophytic Bacteria and Arbuscular Mycorrhizal Fungi in Suppressing Ralstonia solanacearum in Eucalyptus pellita PlantsBacterial wilt disease (BWD) caused by Ralstonia solanacearum is one of the important diseases of eucalyptus (Eucalyptus pellita) plants in Indonesia. One of the control technique approaches is the use of endophytic bacteria and arbuscular mycorrhizal fungi (AMF). This study was aimed to evaluate the effectiveness of endophytic bacteria and AMF in suppressing the development of bacterial wilt disease. There were ten combinations of endophytic bacteria and AMF that were tested on one month old eucalyptus seeds. Artificial inoculation of R. solanacearum was carried out three months after introduction of endophytic bacteria and AMF. Experiments were carried out in the growth chamber. The observation variables included incubation period, disease incidence, disease rate, aggressiveness of bacterial colonization by R. solanacearum, measurement of phenylalanine ammonia lyase (PAL) activity, and total phenol. The results showed that the combination of B5F1 (Paenibacillus polymyxa and Glomus mosseae) showed the highest suppression ability of the development of bacterial wilt disease in eucalyptus seedlings up to 100%. B5F1 treatment showed a longer incubation period of R. solanacearum, the lowest incidence of disease, low infection rates, and inhibited the agresiveness of R. solanacearum. Meanwhile B4F1 (Serratia marcescens and G. mosseae) was able to increase PAL activity and the highest total phenol compared to other treatments. Based on the results of this study, the threatment of B5F1 and B4F1 has the potential to control bacterial wilt disease in eucalyptus plants.